CEO@FACULTY Datuk Ir. Ts. Hj. Wan Nazri Hj. Wan Aria - UiTM, Fakulti Kejuruteraan Awam (Faculty of Civil Engineering, 2025)
As part of the ongoing initiative to strengthen academicindustry engagement under the CEO@Faculty Programme, the Faculty of Civil Engineering is proud to highlight the recent involvement of one of our distinguished CEOS, Datuk Ir. Ts. Hj. Wan Nazri Hj. Wan Aria, in the "Zaman Now" Podcast series. This notable appearance served not only as a platform to showcase his extensive industrial expertise but also as an avenue to share invaluable insights drawn from his professional journey. Through the session, Datuk Wan Nazri inspired alumni, current students, and the broader academic community by addressing contemporary industrial challenges and exploring future opportunities within the civil engineering landscape.